1999
DOI: 10.2223/jped.292
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of hemoglobin

Abstract: Objective: To evaluate the prevalence of Hb S in babies born at the Instituto Materno Infantil de Pernambuco (IMIP) and its occurrence according to sex, birthweight and Apgar.Methods: A cross-sectional descriptive study of all babies born in the IMIP during the period of October/1996 to March/1997 was carried out. Cord blood samples (1,988) were analyzed by alkaline electrophoresis. Data for other infant variables were collected from medical reports. EPI-Info 6.0 was used to analyze the data.Results: We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…The maximum predicted frequency in South America to HbS was about 5% (Piel et al, 2013). In Brazil, a HbS frequency of 0.9 to 14% has been reported (Cardoso et al, 2012;De Mello Auricchio et al, 2007;Bandeira et al, 1999), and in Venezuela, up to 7% HbS has been reported (Salazar-Lugo, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…The maximum predicted frequency in South America to HbS was about 5% (Piel et al, 2013). In Brazil, a HbS frequency of 0.9 to 14% has been reported (Cardoso et al, 2012;De Mello Auricchio et al, 2007;Bandeira et al, 1999), and in Venezuela, up to 7% HbS has been reported (Salazar-Lugo, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…A AF é a doença monogênica mais comum no Brasil. O gene responsável pela doença é um gene de alta frequência em toda a América, e no Brasil é mais frequente nas regiões sudeste e nordeste, chegando a acometer 0,1 a 0,3% da população de pele negra, com tendência a atingir uma parcela cada vez mais significativa da população, devido ao alto grau de miscigenação no país (32,33). É uma doença que apresenta sérias manifestações clínicas, constituindo um problema de saúde pública no Brasil (34).…”
Section: Anemia Falciformeunclassified